2008
DOI: 10.1159/000135639
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative Effect of Vitamin A and D Analogues on Adult Human Keratinocytes in vitro

Abstract: Background: Vitamin A and D analogues play an important role in epidermal homeostasis and are used in the treatment of various skin diseases. The failure of retinoid and vitamin D treatments is sometimes difficult to explain. Methods: We analyzed the effect of all-trans retinoic acid (all-trans RA), 13-cis retinoic acid (13-cis RA), ergocalciferol and cholecalciferol in keratinocyte cultures established from adult donors, on the cell proliferation by means of [3H]thymidine incorporation and apoptosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 66 publications
1
16
0
2
Order By: Relevance
“…CYP26 and CYP24 (19,32) were detectable in our PPC system; thus the usual down-regulatory systems for these vitamins appear to be absent in our PPC preparations. Whilst atRA and calcitriol can have antagonistic effects on each other [19,32] this seems unlikely to be the case in our PPC system since co-treatment with atRA and calcitriol had no such effects. Thus, the mechanisms for regulation of the effects of vitamin A and D in our PPCs require further investigation.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…CYP26 and CYP24 (19,32) were detectable in our PPC system; thus the usual down-regulatory systems for these vitamins appear to be absent in our PPC preparations. Whilst atRA and calcitriol can have antagonistic effects on each other [19,32] this seems unlikely to be the case in our PPC system since co-treatment with atRA and calcitriol had no such effects. Thus, the mechanisms for regulation of the effects of vitamin A and D in our PPCs require further investigation.…”
Section: Discussionmentioning
confidence: 73%
“…atRA and calcitriol act synergistically through RXR:VDR heterodimers to effect many of vitamin D's known effects; they also interact to inhibit the proliferation of breast (MCF-7) and ovarian cancer (NIH:OVCAR3) [30] and promote the differentiation of human promyeloid leukemia cells (HL-60) into monocytes [31]. The RAR and VDR can each heterodimerize with the retinoid X receptor (RXR), accounting for further interactions of the atRA and calcitriol signaling pathways [12,19,[32][33][34] and also of the cytochrome P450 superfamily enzymes CYP26 and CYP24 [12,19,35]. AtRA also down-regulates cellular levels of CYP24 while enhancing the actions of calcitriol [35].…”
Section: Introductionmentioning
confidence: 99%
“…Os 2 mecanismos principais são via VDR, que regula a expressão génica ao estimular a síntese de inibidores do ciclo celular como as proteínas p21 e p27, e por efeito não genómico que leva ao influxo de cálcio nas células alvo, o que estimula a sua diferenciação. [47][48][49][50] Os carcinomas espinocelulares e basocelulares apresentam em mais de 50% "assinatura UV", e in vitro a aplicação tópica de vitamina D parece acelerar a clearance dos dímeros de ciclobutano resultantes de lesão do DNA pela radiação UV. 51 Estudos in vitro e in vivo em modelos de carcinogénese cutânea em ratos têm mostrado que a vitamina D, por diversos mecanismos, teria um efeito supressor nas vias fisiopatológicas dos CEC e CBC.…”
Section: Níveis Adequados De Vitamina Dunclassified
“…The susceptibility of keratinocytes to the antiproliferative effects of vitamins A and D has been reported. 27 It was documented that the observed inhibition of proliferation of mouse and human keratinocytes in vitro by retinoic acid is mediated by independent mechanisms to Peroxisome proliferator-activated receptors (PPAR) receptors an inconsistent notion that RA potentiates cell proliferation by activating PPARb/D. 28 Another report demonstrated that alltransRA, an isoform of RA, increased aquaporin 3 expression and enhanced its biological activity in human skin.…”
Section: Could Diet Affect Acne?mentioning
confidence: 99%